2023
DOI: 10.1021/acsomega.3c03563
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Combustion Characteristics of Activated Carbon Modified via Liquid Phase Impregnation during Drying

Qing-en Li,
Bing J. Zhang,
Shu-shen Lyu
et al.

Abstract: Spontaneous combustion characteristics are important issues for the safe operation of the wet-modified activated carbon drying process. The spontaneous combustion characteristics of activated carbon modified via liquid phase impregnation were fully investigated in this study. The modified activated carbon was prepared using columnar activated carbon and 4-amino-1,2-butanediol solution. Physical properties and surface functional group analyses were performed for activated carbon before and after modification. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
0
0
2
Order By: Relevance
“…Given that the reported temperatures were the operating temperatures (i.e., air temperature) and not the temperatures within the solid matrix, localized temperatures where the reaction takes place may be higher (or lower). GAC has the potential to autoignite at temperatures >450 °C in air or inert atmospheres due to its oxygenated functional groups . In this study, below 800 °C, we did not observe autoignition of the GAC.…”
Section: Resultscontrasting
confidence: 49%
See 1 more Smart Citation
“…Given that the reported temperatures were the operating temperatures (i.e., air temperature) and not the temperatures within the solid matrix, localized temperatures where the reaction takes place may be higher (or lower). GAC has the potential to autoignite at temperatures >450 °C in air or inert atmospheres due to its oxygenated functional groups . In this study, below 800 °C, we did not observe autoignition of the GAC.…”
Section: Resultscontrasting
confidence: 49%
“…GAC has the potential to autoignite at temperatures >450 °C in air or inert atmospheres due to its oxygenated functional groups. 55 In this study, below 800 °C, we did not observe autoignition of the GAC. Above 800 °C, an observed reddish glow to the GAC indicated that either autoignition and/or smoldering might have occurred.…”
Section: ■ Results and Discussioncontrasting
confidence: 37%